The Communication Style of Gibran Rakabuming on Twitter from a SymbThe Communication Style of Gibran Rakabuming on Twitter from a Symbolic Interactionism Perspectiveolic Interactionism Perspective - makmun, fariza (Jurnal Komunikasi Islam dan Kehumasan (JKPI), 2024)
This study analyzes the communication style of Gibran Rakabuming on social media platform X using the perspective of symbolic interactionism. As a prominent young figure in politics who frequently demonstrates unique communication methods on social media, Gibran uses these platforms to build his self-identity and interact with the public. Through a literature review, this research reveals how the symbols, meanings, and interactions Gibran creates on social media reflect the process of identity formation and how the public responds to them. The findings show that from the perspective of symbolic interactionism, Gibran Rakabuming's communication style can be understood as a process of symbolic interaction between Gibran and his audience on social media. He employs symbols such as casual language, humor, and a minimalist communication style to create a strong and memorable impression. Thus, symbolic interactionism helps explain how Gibran utilizes symbols in his political communication to influence public opinion and enhance his electability.